The Examınatıon Of The Effect Of Topıcal Fluorıde Treatment On The Enamel Surface In The S.E.M - Müfide Dinçer (Galenos Yayinevi, 1989)
The study was undertaken to determine the effect of topical fluoride treatment on the enamel surface in the direct bonding system. In this in vitro study, the enamel surfaces of the sample teeth that were subjected to the acidic phosphate fluoride treatment, the basic phosphate fluoride treatment and the only ortophosphoric acid treatment were examined in the S.E.M. Scanning electron photomicrographs were taken at magnifications x2000 and x5000. The overall etching effect on the enamel surface treated with the basic phosphate fluoride solution was very similar to sample surface etched with orthophosphoric acid. It was concluded that there wasn't any differences about mechanical retention speciality at surface characteristics.